1,3,4-Thiadiazole Scaffold: As Anti-Epileptic Agents - Anthwal, Tulika; Nain, Sumitra (Frontiers in Chemistry, 2022)
A wide range of biological activities is exhibited by 1,3,4-thiadiazole moiety such as antidiabetic, anticancer, anti-inflammatory, anticonvulsant, antiviral, antihypertensive, and antimicrobial. To date, drugs such as butazolamide, and acetazolamide. Several modifications have been done in the 1,3,4-thiadiazole moiety which showed good potency as anticonvulsant agents which are highly effective and have less toxicity. After in-depth literature survey in this review, we have compiled various derivatives of 1,3,4-thiadiazole scaffold as anticonvulsant agents.